Simfonije za dve violini in bas = Symphonies for Two Violins and Bass - Ivančič, Amandus (Monumenta artis musicæ Sloveniæ, 1984)
Amandus Ivanschiz (in Slovenian literature "Ivančič") belongs to a group of today little known 18th-century composers. He was, however, in his own time all over Central Europe well known and largely copied monastic composer. Around 200 compositions survived to this date in various copies now preserved in Slovenian, Croatian, Austrian, Czech, etc. archives. However, only a few of his compositions are available to modern performers. In volume 3 of the Monumenta artis musicae Sloveniae series are published three "Simphoniae" for two violins and bass, i.e. triosonatas, typical for Viennese musical circles of the 1750s and 1760s. The music is accompanied by an introductory presentation of the composer's works and Revision Report by Danilo Pokorn (1984).The digitized version of the edition (2020) includes a New Introduction as well as Corrigenda by Maciej Jochymczyk bringing to the reader's attention new information on father Amandus and corrigenda of the earlier edition.